Formation of Bubble-Loop Complexes During Helium Radiation in Fe-9Cr Steel - Shi, Tiantian; Liu, Wenbo; Su, Zhengxiong; Yan, Xu; Lu, Chenyang; Yang, Zhaoxi; He, Xinfu; Yan, Wei; Yun, Di (Frontiers in Energy Research, 2021)
In the present study, the Fe-9Cr model alloy was irradiated with 240 keV He2+ at 550°C with a dose of 0.5 dpa at the peak damage region. The depth distribution of bubbles in Fe-9Cr alloy was investigated by transmission electron microscopy (TEM). The experimental results revealed that the spatial distribution of bubbles along the depth is different. In the region with higher helium concentration and irradiation dose, the bubbles inclined to be situated inside the plane of loops, forming a structure of “bubble-loop complex.” However, in regions where the helium concentration and irradiation dose are relatively low, the number of “bubble-loop complexes” significantly decreased. In addition, the Burgers vector of “bubble-loop complexes” was identified as <100> type. Radiation-induced enrichment of Cr atoms at the “bubble-loop complexes” was also quantitatively estimated by energy-dispersive X-ray spectroscopy (EDS) in the scanning TEM mode.